144 Side effects of sacubitril/valsartan influence outcomes in heart failure populations: a retrospective study. (4th June 2021) - He, Hejie; Kumar, Sheethal; Kuehl, Michael; Aggour, Hesham; Osman, Faizel; Lachlan, Thomas
Abstract : Introduction: Sacubitril/Valsartan (SV) is an effective treatment for patients with heart failure and reduced ejection fraction (HFrEF), decreasing hospitalisation and reducing the overall the risk of cardiovascular death. 1 In the PARADIGM study a higher rate of hypotension and nonserious angioedema was found in the SV vs enalapril arm, but a lower incidence of renal impairment, hyperkalaemia and cough. Until now, there is little data on tolerance of SV outside this clinical trial as well as the consequence of the discontinuation of this therapy. We therefore analysed the side effects of SV in a real-world practice and investigated the outcomes of stopping SV. Methods: We conducted a retrospective analysis of consecutive patients with heart failure and reduced ejection fraction who were started on SV at University Hospitals Coventry and Warwickshire NHS Trust between March 2017 and July 2020. All data points were retrieved from the hospital database up to March 2021. Results: A total of 147 patients were analysed with a mean follow-up of 27.2±8.8 months ( table 2 ) . 17 (12%) patients stopped SV ( table 1 ) . Those who stopped SV were more likely to be hospitalised for heart failure (n=5 [29.4%] vs n=8 [6.9%]; p<0.01) or die (n=7 [41.1%] vs n=8 [6.2%]; p<0.01) when compared to those continuing SV ( table 2 ) . Months to hospitalisation and death in those who stopped SV were 11.0±12.7 and 9.9±10.8 respectively ( table 2 ) . When SV was stopped, 10 (58.8%) started an angiotensin-2 converting enzyme inhibitor (ACEi), 1 (6.0%) an angiotensin-2 receptor blocker (ARB), 4 (23.5%) stopped treatment 1 (6.0%) a nitrate and 1 (6.0%) digoxin in place of SV ( table 2 ) . The maximum dose was reached in 44 (30%) of the cohort up to point of data collection. Renal impairment (n=20 [13.6%]) and postural hypotension (n=19 [12.9%]) were the most common reported side effects ( table 2 ) . Reasons for stopping SV were most commonly renal impairment (n= 7 [41%], creatinine increase of 30.6±51.7 at point of stopping entresto), headache/dizziness (n=4, [23.5%] and postural hypotension (n=3 [17.6%]) ( table 2 ) . Discussion: In this real-world retrospective study we could demonstrate that discontinuation of SV is associated with a higher chance of hospitalisation for heart failure and death. 17 (11.5%) patients stopped SV all of which had side effects and 7 (41.2%) died, though the characteristics of patients who stopped SV were older age, male, worse renal function prior to SV and higher incidence of atrial fibrillation ( table 1 ) . In the PARADIGM study the number adverse events was 2247 (rate not available) and 76 (1.8%) patients discontinued SV. Compared to our data discontinuation of SV is much higher possibly due to the cohort in the PARADIGM-HF trial all tolerating max dose initially. We suggest further prospective investigation on how to improve maintain/titrate to max dose SV in cohorts of HFrEF patients who do not tolerate SV well with respect to outcomes. Conflict of Interest: Nil Reference: McMurray JJV, Packer M, Desai AS, et al . Angiotensin–Neprilysin Inhibition versus Enalapril in Heart Failure. N Engl J Med 2014;371 (11):993–1004. doi:10.1056/NEJMoa1409077